Isolation and purification of protein (Conglutin-γ) from lupin seeds - Mane, Sharmilee (Curtin University, 2017)
This research focuses on the development of a scalable process for purification of ‘glucose modulating bioactive’, γ-conglutin from lupin seeds. Selective extraction at acidic pH and cation exchange chromatography with an intermediate pH modulation step enabled the isolation of γ-conglutin with highest reported purity in minimum process steps. The effect of process parameters was optimized to obtain the maximum purity. γ-Conglutin purified by the developed process was confirmed for its identity by different analytical techniques.